2010
DOI: 10.4161/chan.4.1.10366
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of cholesterol sensitivity of Kir channels: Role of the CD loop

Abstract: Kir channels are important in setting the resting membrane potential and modulating membrane excitability. A common feature of Kir2 channels and several other ion channels that has emerged in recent years is that they are regulated by cholesterol, a major lipid component of the plasma membrane whose excess is associated with multiple pathological conditions. Yet, the mechanism by which cholesterol affects channel function is not clear. We have recently shown that the sensitivity of Kir2 channels to cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 36 publications
4
65
0
Order By: Relevance
“…[13][14][15][16] However, in CCD cells, our data indicate that ROMK1 is not located in cholesterolrich lipid rafts but mainly, the planar regions of the apical membrane and that the cholesterol-lowering drug, lovastatin, does not alter ROMK1 channel activity in the CCD cells when PI(4)P5K I g expression is significantly reduced. These results suggest that the endogenous cholesterol levels in the planar regions, at least under resting conditions, are unable to reach the threshold that is required to directly inhibit ROMK1 channels but indirectly regulate ROMK1 channels through PI(4)P5K.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…[13][14][15][16] However, in CCD cells, our data indicate that ROMK1 is not located in cholesterolrich lipid rafts but mainly, the planar regions of the apical membrane and that the cholesterol-lowering drug, lovastatin, does not alter ROMK1 channel activity in the CCD cells when PI(4)P5K I g expression is significantly reduced. These results suggest that the endogenous cholesterol levels in the planar regions, at least under resting conditions, are unable to reach the threshold that is required to directly inhibit ROMK1 channels but indirectly regulate ROMK1 channels through PI(4)P5K.…”
Section: Discussionmentioning
confidence: 60%
“…16 Because cholesterol is a component of lipid rafts, 18,29 we originally hypothesized that ROMK1 might be in lipid rafts and that endogenous cholesterol could directly regulate the channel. Surprisingly, our data from sucrose gradient experiments showed that the ROMK1 channel was detected mainly in nonlipid raft membranes ( Figure 3, A and B).…”
Section: Romk1 Is Not Located In Cholesterol-rich Lipid Raftsmentioning
confidence: 99%
See 3 more Smart Citations